Therapeutic Antibodies by Phage Display - Shim, Hyunbo (Current Pharmaceutical Design, 2016)
Background: Antibody phage display is a major technological platform for the generation of fully human antibodies for therapeutic purposes. The in vitro binder selection by phage display allows researchers to have more extensive control over binding parameters and facilitates the isolation of clinical candidate antibodies with desired binding and/or functional profiles. Methods: Since the invention of antibody phage display in late 1980s, significant technological advancements in the design, construction, and selection of the antibody libraries have been made, and several fully human antibodies generated by phage display are currently approved or in various clinical development stages. Results: In this review, the background and details of antibody phage display technology, and representative antibody libraries with natural or synthetic sequence diversity and different construction strategies are described. The generation, optimization, functional and biophysical properties, and preclinical and clinical developments of some of the phage display-derived therapeutic antibodies approved for use in patients or in late-stage clinical trials are also discussed. Conclusion: With evolving novel disease targets and therapeutic strategies, antibody phage display is expected to continue to play a central role in the development of the next generation of therapeutic antibodies.
Keywords: synthetic antibody libraries